A Comparison of Oxygen Fugacities of Strongly Peraluminous Granites across the Archean–Proterozoic Boundary. (18th October 2018) - Bucholz, Claire E; Stolper, Edward M; Eiler, John M; Breaks, Frederick W
Abstract: We constrain the oxygen fugacity (f O 2 ) of strongly peraluminous granites [SPGs; i.e. granites ( sensu lato ) generated through the partial melting of sediments] across the Archean–Proterozoic boundary, which coincides roughly with the Great Oxygenation Event (GOE), to understand whether secular changes in atmospheric O2 levels may be imprinted on the f O 2 of igneous rocks. SPGs were chosen to maximize the potential effects of sediments in their sources on the f O 2 of the magmas. We studied 28 Archean (2685–2547 Ma) and 31 Meso- to Paleoproterozoic (1885–1420 Ma) geographically distributed samples from North America, spanning two cratons (Superior and Wyoming) and both orogenic and anorogenic Proterozoic provinces (Trans-Hudson Orogen, Wopmay Orogen, and SW USA). We present an analysis of both new and previously published whole-rock major and trace element data and mineral major element chemistry from the samples. All the studied samples are peraluminous high-silica plutonic rocks (all contain >67 wt % SiO2, and 92% are true granites with >69 wt % SiO2 ), and biotite + muscovite ± garnet ± tourmaline ± sillimanite are the primary aluminous minerals in all samples. Whole-rock major element and trace element abundances of all samples are consistent with derivation by partial melting of aluminous sediments. To constrain the f O 2 of crystallization of the SPGs, we developed an alphaMELTS-based method that takes advantage of the sensitivity of biotite Fe T /(Fe T + Mg) ratios to f O 2 . This method is able to reproduce experimental and empirical data where biotite compositions and whole-rock compositions, pressures and temperatures of crystallization and f O 2 are known. For the SPGs in this study, alphaMELTS modeling indicates that 68% of Proterozoic samples crystallized at an f O 2 between NNO –1 and NNO +1·1 (where NNO is nickel–nickel oxide buffer), whereas the remaining Proterozoic samples (32%) and most of the Archean samples (75%) crystallized at ≤NNO –2. The simplest explanation of these results is that the Proterozoic SPGs were derived from metasedimentary source rocks that on average had more oxidized bulk redox states relative to their Archean counterparts. The bulk redox state of the metasedimentary source rocks of SPGs of all ages is defined by the relative abundances of oxidized (e.g. Fe 3+ and S 6+ ) and reduced (e.g. organic matter) material. The crystallization of both Archean and Proterozoic samples at f O 2 values of ≤NNO –2 is consistent with them having their f O 2 buffered by graphite (formed from organic carbon) in their source regions. However, the dominantly low f O 2 (≤NNO –2) values of the Archean SPGs plausibly reflects the presence of organic material and relatively reduced metasedimentary rocks in their source region prior to the GOE. In contrast, the elevated f O 2 values of the majority of the Proterozoic SPGs may reflect enhanced sulfate contents or increased Fe 3+ /Fe T in sediments after the GOE, which, in terms of the bulk redox state of their metasedimentary source region, would have offset the reducing nature of organic matter present there.